Platelet-covered nanocarriers for targeted delivery of hirudin to eliminate thrombotic complication in tumor therapy - Zhang, Kai (2023)
Most patients are at high risk of thrombosis during cancer treatment. However, the major discrepancy in the therapeutic mechanisms and microenvironment between tumors and thrombosis makes it challenging for a panacea to treat cancer while being able to eliminate the risk of thrombosis. Herein, we developed a biomimetic MnOx/Ag2S nanoflower platform with platelet membrane modification (MnOx@Ag2S@hirudin@platelet membrane: MAHP) for the long-term release of anticoagulant drugs to treat thrombosis together with tumor therapy. This MAHP platform could achieve the targeted delivery of hirudin to the thrombus site and perform the controlled release under the irradiation of near-infrared light, demonstrating effective removal of the thrombus. Moreover, MAHP could inhibit tumor progression and prolong the survival time of mice with thromboembolic complications.